Puerperal gravid process like risk factor for the presentation of severe clinical pictures of Influenza A (H1N1) - Carlos Zerquera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
An analysis is carried out about some factors that are considered implied in the normal development of the puerperal gravid process, and that should be kept in mind at the moment to consider the pregnant and postpartum women like a group of risk to suffer severe clinical pictures of Influenza A (H1N1), in the course of the current pandemic. Such considerations are the author's points of view, based on the review of medical literature, as very recent aspects in relation with to the beginning and normal development of the pregnancy and an experience of more than thirty years as the head of medical team for the care of severe pregnant women patients.